Das ostras, só as pérolas: arqueologia pública e arqueologia subaquática no Brasil - Bruno Sanches Ranzani da Silva (2011)
Conflicts between the archaeological practice and the lay public havebecome central issues to the archaeological discipline over the last 30 years. My proposal is to search for experiences and approaches, following the public archaeological perspective, that clarify the political bias of the archaeological knowledge, its responsibility towards society and promote ways of interactions between the discipline and its many different publics. Ill conduct a brief review of the international literature on public archaeology and discuss its applicability to the Brazilian context. Particular attention will be paid to Brazilian underwater archaeology case, since it has been long concerned with its conflicting relationship with recreational divers, mediated by a weak legislation for the protection of the underwater cultural heritage.